THE ROLE AND IMPORTANCE OF CONTINUITY IN THE EDUCATION SYSTEM - Pari Pashayeva (Foundations and Trends in Modern Learning, 2023)
The operation of continuous education is based on the following principles that determine its uniqueness: Humanism Democracy, Mobility Waiting Openness Continuity The principle of humanism testifies to the appeal of education to a person, the freedom of a person to choose the forms, conditions, types of education, professional development and self-education. This principle is implemented by creating favorable opportunities for the development of creative individuality of each person. Man is seen as the goal of social progress. The principle of democracy implies the availability of education at all ages in accordance with interests, possibilities and needs, according to various forms of education. It provides freedom of transfer from one educational institution to another, accelerated education and advanced training. It means equal rights to education and development of all citizens, regardless of class, national characteristics, health status. This principle envisages the democratization of all aspects of the life of educational institutions, equal relations between the subjects of the pedagogical process. The principle of mobility is expressed in the various tools, methods, organizational forms, flexibility of the continuous education system and readiness for rapid restructuring in accordance with the changing needs of production, society and individuals. Focuses on the use of various productive methodological systems and technologies.